Psychology of self-development - Sadirxonova Shoista Abidjanova (Zien Journals, 2022)
The beginning of self-development or the beginning of self-development? In this article, let’s define such self-development, ways of self-development, and what methods of self-development begin with.
Keywords: self-improvement; results; individual; environment